Pembelajaran Pendidikan Agama Islam Melalui Musik Pada Siswa Sekolah Dasar - Khalimah, Siti (Didaktika Religia, 2015)
The study investigates the use of music in Islamic teachings at schoolsas one of the subjects that are usually learned through lectures, speeches, stories, listening, which often makes students feel bored, so the learning process is not effective PAI and the results are not satisfying. Therefore, it is necessary to try the use of music as a medium of instruction to increase the effectiveness of Islamic teachings.The subjects of the study were fifth grade students SDN Kelutan II,Â  Ngronggot, Nganjuk, East Java. The results showed that the use of music for fifth grade students at SDN Kelutan II improves the effectiveness of Islamic teaching cognitively and affectively.Â  In cycle 1 researcher used music as a medium of learning Islamic teachings and the students enjoyed, and felt happy and comfortable. Final evaluation shows that as many as 9 students or 34.6% were not satisfactory while 17 students or 65.4% were satisfactory. After the second cycle, all students completed the task satisfactorily.